2002
DOI: 10.1093/ndt/17.7.1218
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of genotype-phenotype correlation in X-linked Alport syndrome: impact on clinical counselling

Abstract: Knowledge of the mutation adds significant information about the progress of renal and extrarenal disease in males with X-linked AS. We suggest that the considerable prognostic relevance of a patient's genotype should be included in the classification of the Alport phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
223
3
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(258 citation statements)
references
References 44 publications
16
223
3
11
Order By: Relevance
“…2 This milder phenotype is associated with unique genotypes such as missense or in-frame variants in COL4A5. [3][4][5] We previously reported a male XLAS patient with a missense COL4A5 variant who showed only hematuria without proteinuria at the age of 33. 18 We also reported a male patient with a somatic COL4A5 variant who showed hematuria and mild proteinuria at the age of 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This milder phenotype is associated with unique genotypes such as missense or in-frame variants in COL4A5. [3][4][5] We previously reported a male XLAS patient with a missense COL4A5 variant who showed only hematuria without proteinuria at the age of 33. 18 We also reported a male patient with a somatic COL4A5 variant who showed hematuria and mild proteinuria at the age of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 These two phenotypes are partially related to the genotype; for example, missense variants or in-frame variants of COL4A5 were reported in cases of later-onset ESRD. [3][4][5] We recently reported that 29% of male XLAS patients expressed the α5(IV) chain in the glomerulus and showed milder clinical manifestations. 6 Interestingly, all α5(IV)-positive patients possessed non-truncating variants (n = 13) or somatic mosaic variants (n = 2) of COL4A5.…”
Section: Introductionmentioning
confidence: 99%
“…This is due, at least in part, to differences in the severity of COL4A5 mutations, as indicated by the demonstration of genotype-phenotype correlations (albeit less robust than correlations in other renal diseases) (3,4). More specifically, associations between the type of mutation and the clinical evolution were observed after patients were grouped per category of mutation (3,4,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically the natural history of the nephropathy and other extrarenal lesions are quite variable. A number of researchers have attempted to link genotypes in Alport syndrome to phenotypes (Bekheirnia et al, 2010, Gross et al, 2002, Jais et al, 2000. Gross and colleagues have proposed a classification linking phenotype and genotype into three categories (Gross et al, 2002).…”
Section: Genotype-phenotype Correlation In X-linked Alport Syndromementioning
confidence: 99%
“…A number of researchers have attempted to link genotypes in Alport syndrome to phenotypes (Bekheirnia et al, 2010, Gross et al, 2002, Jais et al, 2000. Gross and colleagues have proposed a classification linking phenotype and genotype into three categories (Gross et al, 2002).  Type S (severe); genotypic alterations in COL4A5 include major gene rearrangements, premature stop codons, frameshift mutations, and donor splice site alterations.…”
Section: Genotype-phenotype Correlation In X-linked Alport Syndromementioning
confidence: 99%